If \(a+b+c=0\), find the value of \(\frac{a+b}{c}-\frac{2 b}{c+a}+\frac{b+c}{a}\).
(a) 0
(b) 1
(c) -1
(d) 2
If a+b+c=0, find the value of (a+b)/c-2b/(c+a)+(b+c)/a. (a) 0 (b) 1 (c) -1 (d) 2
Share
Lost your password? Please enter your email address. You will receive a link and will create a new password via email.
Please briefly explain why you feel this question should be reported.
Please briefly explain why you feel this answer should be reported.
Please briefly explain why you feel this user should be reported.
Given the equation \(a + b + c = 0\), we can solve for one of the variables in terms of the others. Without loss of generality, let’s solve for \(c\):
\[
c = -a – b
\]
Substituting this into the given expression:
\[
\frac{a+b}{c} – \frac{2b}{c+a} + \frac{b+c}{a} = \frac{a+b}{-a-b} – \frac{2b}{-a-b+a} + \frac{b-a-b}{a}
\]
This simplifies further to:
\[
\frac{a+b}{-a-b} – \frac{2b}{-b} + \frac{-a}{a}
\]
Since \(\frac{a+b}{-a-b} = -1\) (because the numerator is the negation of the denominator), and \(\frac{-a}{a} = -1\), the expression further simplifies to:
\[
-1 + \frac{2b}{b} – 1 = -1 + 2 – 1
\]
\[
= 2 – 2 = 0
\]
Thus, the value of the given expression, under the condition that \(a + b + c = 0\), is \(0\).
Answer: (a) 0.